Dapagliflozin, sildenafil and their combination in monocrotaline-induced pulmonary arterial hypertension - Yi Tang; Siyuan Tan; Minqi Li; Yijin Tang; Xiaoping Xu; Qinghai Zhang; Qinghua Fu; Mingxiang Tang; Jin He; Yi Zhang; Zhaofen Zheng; Jianqiang Peng; et al. (BMC Pulmonary Medicine, 2022)
Abstract Background Dapagliflozin, a selective inhibitor of sodium-glucose cotransporter 2 (SGLT2), can reduce cardiovascular events and mortality in patients with heart failure. A number of mechanisms have been proposed to explain the beneficial effects of SGLT2 inhibitors. The purpose of this study was to determine whether dapagliflozin can improve pulmonary vascular remodelling and the efficacy of dapagliflozin as an add-on therapy to sildenafil in rats with pulmonary arterial hypertension (PAH). Methods A monocrotaline (MCT)-induced PAH rat model was used in our study. MCT-injected rats were randomly divided into four groups and treated for 3 weeks with daily per os treatment with vehicle, dapagliflozin (1 mg/kg/day), sildenafil (25 mg/kg/day), or a combination of dapagliflozin (1 mg/kg/day) and sildenafil (25 mg/kg/day). Haemodynamic measurements, histological analysis, enzyme-linked immunosorbent assay and western blotting analysis were employed to detect the changes in PAH rats after treatments. Results Dapagliflozin significantly attenuated MCT-induced increases in right ventricular systolic pressure (RVSP) and right ventricular hypertrophy (RVH) in PAH rats. Dapagliflozin effectively decreased the thickening of pulmonary artery media and decreased the muscularization of pulmonary arterioles in PAH rats. Moreover, dapagliflozin attenuated nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome activation in lung tissues and the levels of interleukin-1β (IL-1β) and interleukin-18 (IL-18) in plasma. However, dapagliflozin as an add-on therapy to sildenafil in rats with PAH did not show a more pronounced beneficial effect on right ventricular systolic pressure and pulmonary vascular remodelling in MCT rats than sildenafil alone. Conclusions Dapagliflozin reduces right ventricular systolic pressure and pulmonary vascular remodelling in a rat model of PAH. However, combination therapy with dapagliflozin and sildenafil was not more effective than monotherapy with sildenafil in PAH rats.